A comparison of self-and superior-appraisals of divisional level managers' performance in selected Australian Companies - Teoh, Hai Yap (Penerbit Universiti Kebangsaan Malaysia, 1995)
This study reported the results of a comparison between self- and superior appraisals of divisional level managers' performance in selected Australian manufacturing companies, in terms of four psychometric properties: leniency errors, halo effects, convergent validity and discriminant validity. Significant differences existed between the managers' and their superiors' appraisals based on these criteria. The findings from this study provided further evidence on the performance appraisals issue and suggested that the exclusive use of the self-appraisal method in performance evaluation research should be viewed with caution. Further research using different settings and at different organisational levels would be warranted.